2020
DOI: 10.2196/15863
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of One-Way Text Messaging on Attendance to Follow-Up Cervical Cancer Screening Among Human Papillomavirus–Positive Tanzanian Women (Connected2Care): Parallel-Group Randomized Controlled Trial

Abstract: Background Rapid human papillomavirus (HPV) DNA testing is an emerging cervical cancer screening strategy in resource-limited countries, yet it requires follow-up of women who test HPV positive. Objective This study aimed to determine if one-way text messages improved attendance to a 14-month follow-up cervical cancer screening among HPV-positive women. Methods This multicenter, parallel-group randomized con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 19 publications
3
51
2
Order By: Relevance
“…4 Surprisingly in our study (mobile application and telemedicine) were not the preferred method and this is likely due to similar technology-specific reasons described by Scott Kruse et al, 19 and we need better ways to assess the quality and effectiveness of mobile health applications. 20 Linde et al examined the effectiveness of one-way text messages 7 and similar to our finding, it is not a preferred communication method. Our study shows that the vast majority of responders preferred to use patient-accessible electronic health records (PAEHRs); and the rates found in our study are higher than those reported by Zanaboni et al 21 These results suggest that our cancer patients are willing to use new technologies to enhance patients experience and access to care.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…4 Surprisingly in our study (mobile application and telemedicine) were not the preferred method and this is likely due to similar technology-specific reasons described by Scott Kruse et al, 19 and we need better ways to assess the quality and effectiveness of mobile health applications. 20 Linde et al examined the effectiveness of one-way text messages 7 and similar to our finding, it is not a preferred communication method. Our study shows that the vast majority of responders preferred to use patient-accessible electronic health records (PAEHRs); and the rates found in our study are higher than those reported by Zanaboni et al 21 These results suggest that our cancer patients are willing to use new technologies to enhance patients experience and access to care.…”
Section: Discussionsupporting
confidence: 70%
“…6 Linde et al examined the effectiveness of one-way text messages and found that they did not improve the attendance rate to follow up among patients with cervical cancer. 7 The desire to increase cancer knowledge was associated with a higher likelihood of utilizing a mobile application (OR 261.53;95% CI:10.13-6748.71). 8 Mobile health applications improved goal adherence for breast cancer survivors by providing real-time feedback and accountability with the health care team.…”
Section: Introductionmentioning
confidence: 98%
“…A web‐based text message platform was developed specifically for this project by an information technology expert. It was inspired by a similar platform developed for another text message study conducted in urban Tanzania 16 . Two types of text messages were prepared and uploaded to the text message platform (Table 1); one for HPV‐positive (A) and one for HPV‐negative (B).…”
Section: Methodsmentioning
confidence: 99%
“…The test analyzes HPV DNA in cervical and vaginal specimens. It detects the presence of 14 high-risk HPV infection types (16,18,31,33,35,39, 45, 51, 52, 56, 58, 59, 66, and 68). The results are automatically interpreted by the careHPV test system and are displayed graphically on the controller monitor screen as either "positive" or "negative".…”
Section: Specimens Testingmentioning
confidence: 99%
See 1 more Smart Citation